2022
DOI: 10.3390/jcm11154547
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Böning et al. Comment on “Ceruti et al. Temporal Changes in the Oxyhemoglobin Dissociation Curve of Critically Ill COVID-19 Patients. J. Clin. Med. 2022, 11, 788”

Abstract: We would like to thank Böning et al. for all the important issues raised in the present commentary [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In their answer to our letter, Ceruti et al (50) conceded that the originally reported low P 50 values resulted from a calculation error and announced a revised paper. They communicated that at the end of the stay surviving patients presented a P 50 of 23.0 + 1.6 compared to 32.2 + 7.9 mmHg in deceased patients.…”
Section: New Publications On Hemoglobin Oxygen Affinity In Covid-19mentioning
confidence: 89%
See 2 more Smart Citations
“…In their answer to our letter, Ceruti et al (50) conceded that the originally reported low P 50 values resulted from a calculation error and announced a revised paper. They communicated that at the end of the stay surviving patients presented a P 50 of 23.0 + 1.6 compared to 32.2 + 7.9 mmHg in deceased patients.…”
Section: New Publications On Hemoglobin Oxygen Affinity In Covid-19mentioning
confidence: 89%
“…Patients in whom oxygen affinity-and thus, oxygen loading in the lungs -increased over the hospital stay had a higher probability of survival (56). In the patients reported by Ceruti et al (50) the P 50 difference between surviving and deceased patients is dramatic: P 50 of 23.0 + 1.6 compared to 32.2 + 7.9 mmHg in the corrected version of their paper!…”
Section: P 50 Calculation From Single Arterial Samplesmentioning
confidence: 91%
See 1 more Smart Citation
“…In clinical settings, however, Hb-O 2 affinity is routinely measured by the oxygen dissociation curve (ODC), a graphical representation of the relationship between oxygen saturation and oxygen partial pressure, where p50 (the oxygen tension when Hb is 50% saturated with oxygen) is used as the sole descriptor of Hb-O 2 affinity, usually calculated under standard conditions (pH: 7.4, PCO 2 : 40 mmHg, temperature: 37 °C) [ 36 , 41 , 182 , 183 ], i.e., in the “artificial normalization” of a potentially very abnormal blood-flow environment in a seriously ill patient, leading to the elimination of many influencing factors that can change the ODC unpredictably [ 43 ], thereby leading to conflicting results [ 184 , 185 ]. Another bottleneck in most previous investigations of Hb-O 2 affinity was that the concentration of 2,3-DPG in RBCs of patients with SARS-CoV-2 infection was not usually measured [ 41 ], and the concentrations of Hb, phosphate, age (aging red cells or patients), history of heart failure [ 39 ], or a fixed value of 2,3-DPG [ 186 , 187 ] were used as a sensitive index in predicting 2,3-DPG concentration. However, the steady-state concentration of 2,3-DPG in RBCs varies widely among patients with the same disease, and does not always correlate with P50, Hb concentration, or plasma phosphate [ 188 , 189 , 190 , 191 ].…”
Section: Potential Causes Of Discrepancies In Available Data and Chal...mentioning
confidence: 99%